In a fish tank, ⅐ of the fish have a red stripe on them. if 18 of the fish have red stripes, how many totad fish are in the tank?

Answers

Answer 1
Answer:

Answer:

total number of fish = 126

Step-by-step explanation:

let n be the total number of fish in the tank , then

(1)/(7) n = 18 ( multiply both sides by 7 to clear the fraction )

7 × (1)/(7) n = 7 × 18

n = 126

total number of fish in the tank is 126


Related Questions

What does the product of any whole-number factor multiplied by 100 always have ? Explain
Translate the phrase into an algebraic expression.3 times b
joe drank 4 liters of water on monday and 4 deciliters of water on tuesday. how much more water did he drink on monday tha on tuesn
The perimeter of a rectangle billboard is 60 feet and has a length 6 feet longer than its width. Find the dimensions of the billboard.
Select the points you need to calculate the average rate of change from the beginning of the slide to when the slide has covered a horizontal distance of 15 feet. (0.80) (5.40) (10. 20) (15. 10)​

Mai bought a television for $325. The tax rate is 8%. Which proportion can be used to find the amount of tax Mai will pay?

A.8/325=x/100

B.8/325=100/x

C.8/100=325/3

D.8/100=x/325

Answers

the answer is
A. 8/225 = x/100

What is the end behavior of the graph of the polynomial function f(x) = –x^5 + 9x^4 – 18x^3?

Answers

Answer: its C

Step-by-step explanation:

hello

For example, the monomial y = x 2 has the following end behavior: y → ∞ as x → −∞ and y → ∞ as x → ∞ 
For any polynomial, the end behavior is determined by the term that contains the highest power of x, because when x is large, the other terms are relatively insignificant in size.

Write the equation of a line that passes through the point (-8,2) and is parallel to the line 3x-2y=12

Answers

Answer:

Step-by-step explanation:

-2y = -3x + 12

2y = 3x - 12

y = 3/2x - 6

y - 2 = 3/2(x + 8)

y - 2 = 3/2x + 12

y = 3/2x + 14

How do you solve:

x-y=3
x-y=7

Answers

\left\{\begin{array}{ccc}x-y=3\nx-y=7&/\cdot(-1)\end{array}\right\n\n+\left\{\begin{array}{ccc}x-y=3\n-x+y=-7\end{array}\right\n---------\n.\ \ \ \ \ \ \ \ 0=-4\ -\ FALSE\n\nAnswer:no\ solution;\ x;\ y\in\O
If you are trying to solve those equations using the equal values method, you would first turn both the equations to equal y. So for x-y=3, you would add y to each side to get x=3+y and then subtract 3 from each side to get x-3=y. When you do the same thing to the equation x=y=7, you get x-7=y. When you plug them together you take away the y's and put an equal sign in between:
                     x-3=x-7  -then you would subtract x from any side and do that to the other side. You get -3=-7 which isn't correct so you would get a "no solution" problem.

Two angle measures in a scalene triangle are 77° and 62°. What is the measure of the third angle? 41°
61°
77°
221°

Answers

Two angle measures in a scalene triangle are 77° and 62°. The measure of the third angle is 41°.

How does an angle form?

An angle requires two straight line/ line segments/rays, such that they're connected on one of their endpoints.

The angle is the degree of rotation that it will take for the moving side to go from the initial side to the position it is currently on.

The total measure of the inner angles of a shape;

(n-2) x 180°

where n is the number of sides.

(3-2)180\n1 * 180

180° is the total measure of the inner angles.

To put that as an equation;

180° = 77° + 62° + x°

x = 41°

Learn more about angles here:

brainly.com/question/27458498

#SPJ2

The total measure of the inner angles of a shape is determined by the expression;
(n-2)*180° where n is the number of sides.
(3-2)180°
1*180°
180° is the total measure of the inner angles.
To put that as an equation; 
180° = 77° + 62° + x°
x = 41°

The inequality −6(x − 3) > 42 is given.Part A: Solve the inequality and show every step of your work. (4 points)

Part B: Explain in words how to graph the solution to the inequality on a number line. (4 points)

Part C: Find two values that would make the inequality true. Explain how you know the values are solutions to the inequality. (4 points)

Answers

Answer: Sure, I can help you with that!

Part A: To solve the inequality −6(x − 3) > 42, we first need to distribute the -6 to the expression inside the parentheses:

-6(x - 3) > 42 -6x + 18 > 42

Next, we’ll subtract 18 from both sides:

-6x > 24

Finally, we’ll divide both sides by -6. Since we’re dividing by a negative number, we need to flip the inequality sign:

x < -4

Therefore, the solution to the inequality is x < -4.

Part B: To graph the solution to this inequality on a number line, we’ll start by drawing an open circle at -4 (since x is not equal to -4). Then, we’ll draw an arrow pointing to the left of -4 to indicate that all values less than -4 are solutions to the inequality.

Part C: To find two values that would make the inequality true, we can choose any two values less than -4 and substitute them into the original inequality. For example, if we choose x = -5, then:

-6(-5 - 3) > 42 -6(-8) > 42 48 > 42

Since 48 is greater than 42, this confirms that x = -5 is a solution to the inequality. Similarly, if we choose x = -10, then:

-6(-10 - 3) > 42 -6(-13) > 42 78 > 42

Since 78 is also greater than 42, this confirms that x = -10 is also a solution to the inequality.

I hope this helps!